THE EFFICACY OF Toona sureni (Bl.) merr LEAF EXTRACT ACROSS DIFFERENT CONCENTRATIONS IN MANAGING TOBACCO CUTWORM (Spodoptera litura F.) INFESTATIONS - Saputra, Yudikat; Brotodjojo, Raden Roro Rukmowati (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Control of S. litura by farmers still depends on the use of synthetic pesticides which are believed to be practical. Toona sureni is a plant that has potential as a vegetable insecticide. This research was carried out at the Plant Protection Laboratory, Faculty of Agriculture, UPN "Veteran" Yogyakarta. The research was structured in a single factor Completely Randomized Design (CRD) with 6 treatments and repeated 3 times. The treatments tried were concentrations of T. sureni suren leaf extract, namely TP: Control without pesticide treatment, T0: control of the synthetic insecticide Deltamethrin, T1: 8% suren leaf extract, T2: 10% suren leaf extract, T3: 12% suren leaf extract, and T4: Suren Leaf Extract 14%. The method used for data collection is direct observation of pests. The parameters observed were larval mortality, larval feeding capacity, larval to pupal phase, percentage of larvae to pupae, larval to imago phase, percentage of larvae to imago, and efficacy. Data were analyzed using analysis of variance (ANOVA). If there is a real difference between each treatment. If it shows a real effect, then proceed with the 5% DMRT test. Application of T. sureni concentrations of 8%, 10%, 12%, and 14% had the same effective effect in increasing S. litura mortality and efficacy.